2022
DOI: 10.1093/brain/awac413
|View full text |Cite
|
Sign up to set email alerts
|

GALC variants affect galactosylceramidase enzymatic activity and risk of Parkinson’s disease

Abstract: The association between glucocerebrosidase (GCase), encoded by GBA, and Parkinson’s disease highlights the role of the lysosome in Parkinson’s disease pathogenesis. Genome-wide association studies (GWAS) in Parkinson’s disease have revealed multiple associated loci, including the GALC locus on chromosome 14. GALC encodes the lysosomal enzyme galactosylceramidase (GalCase), which plays a pivotal role in the glycosphingolipid metabolism pathway. It is still unclear whether GALC is the gene driving the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…This important issue can be addressed by complementing GWAS data with quantitative trait loci (QTL) datasets correlating risk genotypes with gene expression, methylation, and proteomic data (i.e., Mendelian randomization studies—MRS); this knowledge of the molecular mechanisms by which genetic variants localized in PD risk loci increase the disease risk is a key step to translating genetic evidence into possible therapeutic targets. Remarkably, the link between endolysosomal impairment and synaptic dysfunction within PD derives also from these approaches, which have recently confirmed the causal role of several “lysosomal” and “synaptic” genetic hits (i.e., ARSA , CTSB , GALC , IDUA , RAB29 , RAB7L1 , SH3GL2 , SMPD1 , STX1B , TMEM175 , VAMP42 , and ZSWIM7 ) [ 333 , 343 , 345 , 346 , 347 , 348 , 349 ].…”
Section: Genetic Risk Factors For Pd Associated With Endolysosomal Dy...mentioning
confidence: 95%
See 1 more Smart Citation
“…This important issue can be addressed by complementing GWAS data with quantitative trait loci (QTL) datasets correlating risk genotypes with gene expression, methylation, and proteomic data (i.e., Mendelian randomization studies—MRS); this knowledge of the molecular mechanisms by which genetic variants localized in PD risk loci increase the disease risk is a key step to translating genetic evidence into possible therapeutic targets. Remarkably, the link between endolysosomal impairment and synaptic dysfunction within PD derives also from these approaches, which have recently confirmed the causal role of several “lysosomal” and “synaptic” genetic hits (i.e., ARSA , CTSB , GALC , IDUA , RAB29 , RAB7L1 , SH3GL2 , SMPD1 , STX1B , TMEM175 , VAMP42 , and ZSWIM7 ) [ 333 , 343 , 345 , 346 , 347 , 348 , 349 ].…”
Section: Genetic Risk Factors For Pd Associated With Endolysosomal Dy...mentioning
confidence: 95%
“…GALC encodes galactosylceramidase, a lysosomal hydrolase involved in ceramide catabolism, similar to ASAH1 , GBA1 , and SMPD1 [ 13 , 21 , 341 , 342 ]. Interestingly, the GALC rs979812 variant seems to be associated with increased enzymatic activity of galactosylceramidase [ 343 ].…”
Section: Genetic Risk Factors For Pd Associated With Endolysosomal Dy...mentioning
confidence: 99%
“…ASAH1, GALC, SMPD1). [3][4][5][6][7] Homozygous or compound heterozygous mutations in ARSA may lead to the autosomal recessive lysosomal storage disorder metachromatic leukodystrophy (MLD). 8 Located on chromosome 22q13.33, the ARSA gene encodes arylsulfatase A, which hydrolyzes sulfatides to galactosylceramide and sulfate 8 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, hydrolysis of galactosylceramide occurs by the lysosomal enzyme galactosylceramidase, encoded by GALC, which is nominated as a PD gene by genome-wide association studies and targeted analyses. 6,7,9 The genetic association between ARSA variants and PD remains controversial. [10][11][12][13][14] Cosegregation of pathogenic ARSA variant was reported in one family with two PD patients, and two studies suggested potential association between rare ARSA loss-of-function variants and PD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation